FINANCIAL LITERACY LEVEL IN UZBEKISTAN AND WAYS TO IMPROVE IT - Ubaylullayeva Oydinoy Xabibullayevna (Bright Mind Publishing, 2025)
This article examines the current level of financial literacy in Uzbekistan, identifies key challenges and gaps, and proposes effective strategies for improvement. As financial systems become increasingly complex, equipping individuals with financial knowledge and skills is critical for personal and national economic well-being. The paper analyzes national trends, reviews relevant literature, and outlines a set of policy and educational recommendations based on the realities of Uzbekistan.
Keywords: Financial literacy, economic education, personal finance, financial inclusion, policy reform, financial awareness.